Distinctive Effects of Fullerene C60 and Fullerenol C60(OH)24 Nanoparticles on Histological, Molecular and Behavioral Hallmarks of Alzheimer’s Disease in APPswe/PS1E9 Mice - Sholpan Askarova; Kseniia Sitdikova; Aliya Kassenova; Kirill Chaprov; Evgeniy Svirin; Andrey Tsoy; Johannes de Munter; Anna Gorlova; Aleksandr Litavrin; Aleksei Deikin; Andrey Nedorubov; Nurbol Appazov; et al. (Antioxidants)
Fullerenes and fullerenols exhibit antioxidant and anti-inflammatory properties, making them promising candidates for Alzheimer’s disease (AD) therapy. Unlike conventional anti-inflammatory drugs, these compounds have multitargeted effects, including their ability to inhibit amyloid fibril formation. However, few studies have explored their efficacy in high-validity AD models. Female APPswe/PS1E9 (APP/PS1) mice and their wild-type (WT) littermates were orally administered with fullerene C60 (0.1 mg/kg/day) or fullerenol C60(OH)24 (0.15 mg/kg/day) for 10 months starting at 2 months of age. Behavioral assessments were performed at 12 months of age. Amyloid plaque density and size were analyzed in the brain regions using Congo red staining. The expression of genes related to inflammation and plasticity was examined, and an in vitro assay was used to test the toxicity of fullerenol and its effect on amyloid β peptide 42 (Aβ42)-induced reactive oxygen species (ROS) production. Fullerenol reduced the maximum plaque size in the cortex and hippocampus, decreased the small plaque density in the hippocampus and thalamus, and prevented an increase in glial fibrillary acidic protein (GFAP) positive cell density in the mutants. Both treatments improved cognitive and emotional behaviors and reduced Il1β and increased Sirt1 expression. In vitro, fullerenol was non-toxic across a range of concentrations and reduced Aβ42-induced ROS production in brain endothelial cells and astrocytes. Long-term administration of fullerene or fullerenol improved behavioral and molecular markers of AD in APP/PS1 mice, with fullerenol showing additional benefits in reducing amyloid burden.